Ethylene signaling modulates contents of catechin and ability of antioxidant in Camellia sinensis - Shun-Wun Ke; Guan-Heng Chen; Chung-Tse Chen; Jason T. C. Tzen; Chin-Ying Yang (Botanical Studies, 2018)
Abstract Background Tea is one of the most popular beverages in the world. There are many secondary metabolites can be found in tea such as anthocyanins, proanthocyanidins, flavonols and catechins. These secondary metabolites in plants are proved to act protective components for human health effect. Plant hormone ethylene is considered to have an important role in regulation of plant development and signal transduction. This study evaluated the effect of ethylene signaling regulation in phenolic compounds in tea plants. The ethylene precursor 1-aminocyclopropane-1-carboxylic acid (ACC) enhanced contents of total catechin in treated oolong tea seedlings. Results The degree of epigallocatechin and epicatechin galloylation was increased after ACC treatment in oolong tea seedlings by high performance liquid chromatography determination. The contents of anthocyanins, flavonoids, and total polyphenol were higher after ACC treatment in comparison with control. Antioxidant enzyme such as catalase, superoxide dismutase, and total peroxidase decreased their antioxidant activities after ACC treatment, yet the activity of ascorbate peroxidase is increased. The ability of oxygen radical absorption and 2,2-diphenyl-1-picrylhydrazyl was used to evaluate the antioxidant activity, which was enhanced by ACC treatment. Conclusions Taken together the results of this study demonstrate that the ethylene signaling is involved in modulation of secondary metabolites accumulation and antioxidant ability that to enhance the benefit of human health in tea products.